The future risk of primary biliary cholangitis (PBC) is low among patients with incidental anti‐mitochondrial antibodies but without baseline PBC. Issue 11 (23rd August 2022) - Duan, Weijia; Chen, Sha; Li, Shuxiang; Lv, Tingting; Li, Buer; Wang, Xiaoming; Wang, Yu; Zhao, Xinyan; Ma, Hong; Ou, Xiaojuan; You, Hong; Jia, Jidong
Abstract: Anti‐mitochondrial autoantibodies (AMAs) are highly specific for the diagnosis of primary biliary cholangitis (PBC) but are also occasionally found in other diseases. In the present study, we evaluated the incidence of and predictors for PBC development in AMA‐positive patients with other liver or non‐liver diseases at baseline. In this retrospective study, we screened patients who tested positive for AMA and/or anti‐mitochondrial M2 antibody (AMA‐M2) at Beijing Friendship Hospital, Capital Medical University, from October 2005 to January 2017. They were categorized by their diagnosis at the baseline as patients with PBC or non‐PBC cases. We followed up on the non‐PBC cases through telephone interviews and reviewing of medical records to obtain laboratory results and clinical outcomes. In total, 139 patients were AMA‐positive but did not fulfill the diagnostic criteria of PBC at baseline, including 51 patients with non‐PBC liver diseases and 88 cases with non‐liver diseases. The titers of AMA‐M2, alkaline phosphatase, gamma‐glutamyl transpeptidase, and immunoglobulin M were significantly higher in patients with PBC compared to those with non‐PBC liver diseases and non‐liver diseases. After a median follow‐up of 4.6 (interquartile range: 2.4–7.6) years, 4.3% (6 of 139) developed PBC, with an accumulative 5‐year incidence rate of 4.2%. None of the patients with non‐PBC liver diseases developed PBC, whereas the 5‐year incidence rate of PBC was 7.8% among 88 patients with non‐liver diseases. Lower alanine aminotransferase and higher immunoglobulin M were independent predictors for developing PBC. Conclusion : Our results suggest a low risk of developing PBC over time in AMA‐positive patients with other liver and non‐liver diseases. Abstract : In this study, we found that AMA‐positive patients with non‐PBC diseases had a low risk of developing PBC, especially for those with other liver diseases. Higher immunoglobulin M and lower alanine aminotransferase were independent predictors for developing PBC.image